Exergy Assessment of Photovoltaic Thermal with V-groove Collector Using Theoretical study - Muhammad Zohri; Nurato Nurato; Lalu Darmawan Bakti; Ahmad Fudholi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The solution of the environmental problems because of fuel fossil is to use new and renewable energy. There are many studies about energy analysis of solar collector with v-groove but exergy analysis of photovoltaic thermal system with v-groove is still less especially by theoretical study. Photovoltaic thermal with v-groove collector has been conducted the exergy analysis by theoretical assessment. The matrix inversion methods were used to analyze the energy balance equation. The theoretical assessment was conducted under the solar intensity of 385 W/m2, 575 W/m2, and 875 W/m2 and mass flow rate between 0.01 and 0.05 kg/s. The maximum exergy efficiency and exergy of PVT system with v-groove collector were 17.80% and 86.32 Watt at the solar intensity of 875 W/m2.